Development of autooscillating system of vibration frequency sensors with mechanical resonator - Oliynyk, Olga; Taranenko, Yuri; Shvachka, Alexander; Chorna, Olena (Eastern-European Journal of Enterprise Technologies, 2017)
At present, resonator sensors with an auto-oscillating system have a number of advantages in comparison with the known sensors with frequency output. In this case, developed auto-oscillating systems of resonator sensors are very specific; their elements are oriented toward a particular type of resonator and possess a certain degree of nonlinearity, which makes studying and modeling such systems impossible. In the present work, analytical expressions were obtained for the reduction of parameters of mechanical systems of resonators to the lumped ones. This allowed us to apply the methods of research into nonlinear systems of control to the analysis of AOS and to receive the expression of transfer function of nonlinear resonator with consideration to the nonisochronicity. A structure of auto-oscillating system with a nonlinear resonator is devised, which was not explored earlier. With the purpose of selecting the character of nonlinearity in the elements of feedback and mechanical resonator of the assigned type in AOS to warrant the assigned stability of frequency and amplitude of auto-oscillations, we performed imitation simulation in the Matlab Simulink programming environment. The simulation demonstrated that a nonlinear amplifier at work with a nonlinear mechanical resonator provide for the auto-oscillating system that is stable by frequency and amplitude. Thus, auto-oscillating system of the devised structure can be used in the design of vibration frequency sensors.